Programmed death‐ligand 1 expression and use of immune checkpoint inhibitors among patients with advanced non‐small‐cell lung cancer in a resource‐limited country. Issue 11 (3rd May 2022) - How, Soon Hin; Tho, Lye Mun; Liam, Chong Kin; Hasbullah, Harissa H.; Ho, Gwo Fuang; Muhammad Nor, Ibtisam; Poh, Mau Ern; Ho, Kean Fatt; Thiagarajan, Muthukkumaran; Samsudin, Azlina; Omar, Azza; Ong, Choo Khoon; et al.
Abstract: Introduction: Immune checkpoint inhibitor (ICI) therapy is an established treatment for advanced non‐small‐cell lung cancer (NSCLC) and programmed death ligand‐1 (PD‐L1) expression is a recognized biomarker to determine response to therapy. We retrospectively analyzed NSCLC patients in the Malaysia Lung Cancer Registry (MLCR) and report on the clinical characteristics associated with PD‐L1 expression and ICI use in Malaysia, a low‐ to middle‐income country. Methods: All 901 NSCLC patients in the MLCR who were diagnosed from January 1, 2017 to December 31, 2020 from 14 hospitals across the country were analyzed. Results: Out of 901 patients, 505 had PDL‐1 testing done with complete data available only in 489 patients. The most common histology was adenocarcinoma (84.7%) followed by squamous cell carcinoma (10.2%). The majority (95%) presented with stage 3 or 4. The number and percentage of patients with PDL‐1 tumor proportion scores of ≥50%, 1–49%, and <1% were 138 (28.2%), 158 (32.3%), and 193 (39.5%), respectively. In multivariate analysis, the presence of genomic mutation is the only independent characteristic associated with negative PD‐L1 expression (crude odds ratio 0.579, 95% confidence interval 0.399–0.840, p  = 0.004). Of 292 patients eligible for ICI therapy, only 100 patients (34.2%) received ICIs. Seventy‐eight patients received ICI therapy as first‐line treatment, 15 patients as second‐line treatment, and 7 patients as third‐line treatment. Conclusions: This is the first analysis on PD‐L1 expression and ICI use in Malaysia. Despite the proven efficacy of ICI therapy, only 56% of our patients had PD‐L1 tests performed and only 34.2% of eligible patients received ICIs. Abstract : We retrospectively analyzed 901 non‐small‐cell lung cancer patients in the Malaysia Lung Cancer Registry and report on the clinical characteristics associated with programmed death ligand‐1 (PD‐L1) expression and immune checkpoint inhibitor use in Malaysia, a low to middle income country. The majority (95%) of our patients presented with stage 3 or 4. Only 505 had PDL‐1 testing done, with complete data available in 489 patients. The number and percentage of patients with PDL‐1 tumor proportion scores of ≥50%, 1–49%, and <1% were 138 (28.2%), 158 (32.3%), and 193 (39.5%), respectively. In multivariate analysis, the presence of genomic mutation is the only independent characteristic associated with negative PD‐L1 expression (crude odds ratio 0.579, 95% confidence interval 0.399–0.840, p  = 0.004). Of 292 patients eligible for immune checkpoint inhibitor (ICI) therapy, only 100 patients (34.2%) received ICIs. We propose strategies to improve uptake of ICI therapy in countries with limited resources.